Glacigenic sedimentation pulses triggered postglacial gas hydrate dissociation - Karstens, Jens; Haflidason, Haflidi; Becker, Lukas W.M.; Berndt, Christian; Rüpke, Lars; Planke, Sverre; Liebetrau, Volker; Schmidt, Markus; Mienert, Jürgen (Nature Communications, 2018)
Source at https://doi.org/10.1038/s41467-018-03043-z . Large amounts of methane are stored in continental margins as gas hydrates. They are stable under high pressure and low, but react sensitively to environmental changes. Bottom water temperature and sea level changes were considered as main contributors to gas hydrate dynamics after the last glaciation. However, here we show with numerical simulations that pulses of increased sedimentation dominantly controlled hydrate stability during the end of the last glaciation offshore mid-Norway. Sedimentation pulses triggered widespread gas hydrate dissociation and explains the formation of ubiquitous blowout pipes in water depths of 600 to 800 m. Maximum gas hydrate dissociation correlates spatially and temporally with the formation or reactivation of pockmarks, which is constrained by radiocarbon dating of Isorropodon nyeggaensis bivalve shells. Our results highlight that rapid changes of sedimentation can have a strong impact on gas hydrate systems affecting fluid flow and gas seepage activity, slope stability and the carbon cycle.